2008
DOI: 10.1093/rheumatology/ken407
|View full text |Cite
|
Sign up to set email alerts
|

Autologous progenitor cell implantation as a novel therapeutic intervention for ischaemic digits in systemic sclerosis

Abstract: This first open-label pilot study demonstrates the feasibility and short-term safety of local CD34(+) cell therapy for SSc ischaemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 8 publications
4
35
0
3
Order By: Relevance
“…Surgical therapy includes arterial bypass, digital arterial reconstruction, sympathectomy (peripheral and digital) and amputation [12][13][14][15]. Recently botulinum toxin injection and local or intramuscular injection of mesenchymal stem cell have been used in the management of patients with digital ischemia due to secondary RP [16][17][18]. An endovascular procedure, as we present in our case, has not been reported previously in the management of RP.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical therapy includes arterial bypass, digital arterial reconstruction, sympathectomy (peripheral and digital) and amputation [12][13][14][15]. Recently botulinum toxin injection and local or intramuscular injection of mesenchymal stem cell have been used in the management of patients with digital ischemia due to secondary RP [16][17][18]. An endovascular procedure, as we present in our case, has not been reported previously in the management of RP.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic efficacy was associated with restoration of endothelial function, augmentation of microcirculatory blood flow, and significant increase in angiogenesis. 58 A single-institution pilot study reported a significant and rapid decrease of the extent of pulmonary fibrosis associated with SSc observed on HRCT in 9 patients with severe diffuse SSc 6 months after autologous HSCT. The early treatment effects of HSCT on the extent of pulmonary fibrosis decreased over time and were transient in some patients after long-term follow up.…”
Section: Dovepressmentioning
confidence: 98%
“…More recently, in a phase I study, the safety of autologous MSCs-AT was demonstrated in patients with severe lower-limb ischemia without the possibility of revascularization, exhibiting an increase in transcutaneous oxygen pressure and leg ulcer cicatrization [49]. Local injections of autologous MSCs of peripheral blood and BM have been utilized, reporting an improvement in the Raynaud phenomenon and of digital-ulcer and lower-limb cicatrization [50]. Autologous MSCs-AT have been employed in local injection of areas localized of the face, with a reduction of skin thickness [51] and in that of the fingers, with important improvement of the disability, of the edema and of the Raynaud phenomenon [52].…”
Section: Sclerosis Systemic (Ss)mentioning
confidence: 99%